Marine corrosion resistant long life stainless steel wire rope and method of making same

CN119859932BActive Publication Date: 2026-10-16WUXI CITY STRONG STEEL ROPE CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411888766.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2026-10-16
Estimated Expiration
2044-12-20

AI Technical Summary

Benefits of technology

1、本发明结合不锈钢在海洋环境中发生的腐蚀现象,如海水中的氯离子极易在钢中夹杂物缺陷处发生点蚀现象,提出在所制奥氏体不锈钢中添加稀土铈,将上述夹杂物转变为稀土夹杂物,细化晶粒、减少裂纹,形成稳定的钝化膜,提高主体奥氏体不锈钢的耐腐蚀性能,再进行热处理,提高该奥氏体不锈钢盘条的热塑性,降低后期热浸镀锌对钢丝扭转性能的损失,提高镀锌层的质量合格率;热处理后再进行预拉拔、镀锌、退火,提高镀锌层与基体不锈钢材的结合力,消除内应力,再进行拉拔抽丝,对所制不锈钢丝浸涂铝锌涂料,烘烤固化形成耐蚀涂层,再涂封闭涂料钝化,进一步提高涂层的耐腐蚀性能;再涂覆润滑油脂,捻制成绳,降低操作中的材料损耗。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a seawater corrosion resistant long service life stainless steel wire rope and a preparation method thereof, and relates to the technical field of steel wire ropes. The specific steps comprise the following steps: sequentially performing heat treatment, pickling and phosphorization on an austenitic stainless steel wire rod, and then performing 7 passes of continuous drawing to obtain pre-drawn stainless steel wires with a specification of 8-10 mm; then performing hot dip galvanizing on the pre-drawn stainless steel wires after degreasing and water washing, wiping and cooling, and performing annealing treatment; after the annealing treatment is completed, performing 8-10 passes of continuous drawing again to obtain finished stainless steel wires with a specification of 1-3 mm; after degreasing and water washing, performing immersion coating of chromium-free zinc-aluminum coating liquid; after spin-drying, baking and solidification, performing immersion coating of sealing coating liquid; after drying, performing coating of lubricating grease; and adopting parallel twisting to obtain the stainless steel wire rope.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of steel wire rope technology, specifically to a long-life stainless steel wire rope resistant to seawater corrosion and its preparation method. Background Technology

[0002] With the rapid development of science and technology and the national economy, the development and utilization of Earth's poles and marine resources have become a key research and development focus for countries worldwide. Humans have utilized the ocean for thousands of years, initially focusing on coastal and near-shore fisheries, salt production, and transportation. Later, with technological advancements and increased resource demands, marine development entered a new phase, including large-scale development of seabed oil, natural gas, and mineral deposits; the establishment of tidal power stations and desalination plants; and emerging industries such as mariculture, deep-sea mining, and wave power generation. In modern marine development, oil and natural gas development accounts for approximately 70% of the total output value. Industries such as mariculture, desalination, and tidal power generation are also developing rapidly. As my country's marine development and utilization increase, various marine equipment and energy supply issues are arising. For example, most marine equipment is exposed to the marine environment for extended periods, placing high demands on the performance of the materials used. These materials must possess not only excellent mechanical properties but also good corrosion resistance. In marine engineering, stainless steel wire ropes are mainly used in the construction of large offshore platforms, offshore drilling platforms, subsea drilling equipment, oil and gas pipelines, and submarine cables. These applications require the wire ropes to have high strength, wear resistance, and corrosion resistance; in order to ensure the long-term stability and safety of stainless steel wire ropes in the marine environment, continuous optimization of the production process is still necessary. Summary of the Invention

[0003] The purpose of this invention is to provide a long-life stainless steel wire rope resistant to seawater corrosion and its preparation method, so as to solve the problems raised in the prior art.

[0004] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a long-life stainless steel wire rope resistant to seawater corrosion, specifically including the following steps: Step 1: Select austenitic stainless steel wire rod, and perform heat treatment, pickling, and phosphating in sequence, and then draw it through 7 consecutive draws to obtain pre-drawn stainless steel wire with a specification of 8-10mm. Step 2: After degreasing and washing the pre-drawn stainless steel wire obtained in Step 1, hot-dip galvanize it, wipe it to cool it, and then anneal it. After annealing, it is drawn again for 8-10 consecutive times to obtain finished stainless steel wire with a specification of 1-3mm. Step 3: After degreasing and washing the finished stainless steel wire obtained in Step 2, dip it in a chromium-free zinc-aluminum coating solution, spin dry, bake and cure to obtain a coating thickness of 30μm. After cooling, dip it in a sealing coating, dry it and then coat it with lubricating grease. Then, use parallel twisting to obtain a stainless steel wire rope.

[0005] The specific chemical composition of the austenitic stainless steel wire rod in step 1, by mass percentage, includes 16-18% Ni, 14.5-14.7% Cr, 5.5-6.0% Si, 1.02-1.05% Mo, 1.08-1.30% Mn, C≤0.020%, P≤0.020%, S≤0.004%, 0.01-0.05% Ce, and the balance being Fe.

[0006] In step 1, the heat treatment involves heating to 1150-1200℃ at a rate of 10℃ / s, holding at that temperature for 8-12 hours, and then water cooling to room temperature. The zinc layer obtained by hot-dip galvanizing in step 2 has a quality of 200-240 g / m². 2 The annealing temperature is 1000-1100℃ and the annealing time is 2-3 hours.

[0007] The chromium-free zinc-aluminum coating solution in step 3 includes the following raw materials by mass percentage: 15-20% modified flake zinc-aluminum alloy powder, 0.1-0.3% modified graphene, 8-10% ethylene glycol, 6-8% Tween-20, 1-2% hydroxyethyl cellulose, 1.5-2.0% corrosion inhibitor, 10-15% binder, 1-2% defoamer, 30-40% silane hydrolysate, and deionized water to bring the total to 100%. The baking and curing process includes pre-baking at 80-100℃ for 8-10 minutes, followed by baking at 270-320℃ for 12-15 minutes for curing.

[0008] The preparation steps of the modified flake zinc-aluminum alloy powder are as follows: The flake zinc-aluminum alloy powder is pretreated by placing it in anhydrous ethanol, ultrasonically cleaning it for 10 min, rinsing and drying it; silane coupling agent KH570, anhydrous ethanol and deionized water are mixed and stirred, the pH is adjusted to 4, and the mixture is stirred at 35°C for 1 h, and allowed to stand for hydrolysis overnight to obtain KH570 hydrolysate; the pretreated flake zinc-aluminum alloy powder is mixed with the above KH570 hydrolysate, stirred at 40°C for 3 h, an acrylic acid solution diluted with anhydrous ethanol and azobisisobutyronitrile are added, the temperature is raised to 70°C, and stirring is continued for 6 h; the mixture is filtered and washed to obtain the modified flake zinc-aluminum alloy powder.

[0009] The preparation steps of modified graphene are as follows: Add nickel nitrate hexahydrate and rare earth nitrate to deionized water and sonicate for 20 min for later use; place graphene oxide in deionized water, sonicate to disperse it, add sodium citrate and stir for 10 min, place it in the above nitrate solution and sonicate for 20 min, then transfer it to a reaction vessel and react at 160-180℃ for 12 h, cool to room temperature, wash and freeze dry to obtain the modified graphene; Preferably, the rare earth nitrate is any one of cerium nitrate, lanthanum nitrate, and yttrium nitrate.

[0010] The preparation steps for chromium-free zinc-aluminum coating solution are as follows: Step s1: Place zirconium nitrate in deionized water, stir to dissolve, add ethanol and silane coupling agent in sequence, adjust pH to 4-5, stir at 35℃ for 1 hour, let stand for hydrolysis overnight to obtain silane hydrolysate; Step s2: Mix the modified sheet zinc-aluminum alloy powder and ethylene glycol, add deionized water and Tween-20 in sequence and stir evenly, then add modified graphene, hydroxyethyl cellulose, corrosion inhibitor and binder, and continue stirring at 150 r / min for 30 min to obtain metal slurry; Step s3: Mix the silane hydrolysate obtained in steps s1 and s2 with the metal slurry, stir at 1500 r / min for 2-3 h, add the defoamer, and continue stirring at 150 r / min for 20-30 min to obtain the chromium-free zinc-aluminum coating solution.

[0011] In step s1, the silane coupling agent is one or a combination of two of the following: bis-[γ-(triethoxysilane)propyl]-tetrasulfide silane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane, and octadecyltrimethoxysilane.

[0012] The stainless steel wire rope obtained by the above preparation method has an 8×61 structure, including a core and an outer layer of strands; the outer layer of strands adopts a 61FWS structure; the core is composed of an outer core strand and a core center strand, both of which adopt a 36WS structure.

[0013] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention addresses the corrosion phenomena of stainless steel in marine environments, such as the pitting corrosion caused by chloride ions in seawater at inclusion defects in the steel. It proposes adding rare earth cerium to the austenitic stainless steel to transform these inclusions into rare earth inclusions, refining the grains, reducing cracks, forming a stable passivation film, and improving the corrosion resistance of the main austenitic stainless steel. Further heat treatment enhances the thermoplasticity of the austenitic stainless steel wire rod, reduces the loss of torsional properties due to subsequent hot-dip galvanizing, and improves the quality pass rate of the galvanized layer. After heat treatment, pre-drawing, galvanizing, and annealing are performed to improve the bonding strength between the galvanized layer and the base stainless steel, eliminate internal stress, and then the wire is drawn and coated with an aluminum-zinc coating. The coating is then baked and cured to form a corrosion-resistant coating, followed by a passivation coating to further improve the corrosion resistance. Finally, a lubricating grease is applied, and the wire is twisted into a rope, reducing material loss during operation.

[0014] 2. The chromium-free zinc-aluminum coating of this invention uses flake zinc-aluminum alloy powder as the main anti-corrosion material, which is coated and modified to form an acrylic / KH570 protective layer on the zinc-aluminum alloy powder. This improves the dispersibility of the flake zinc-aluminum alloy powder in the coating and enhances the corrosion resistance of the cured coating. Modified graphene is added to the coating. The modified graphene contains nickel oxide and rare earth oxides, which can participate in the network bonding structure of the silane film, disperse evenly, improve the density of the coating, effectively slow down the penetration of corrosive media, and further improve the corrosion resistance of the coating in seawater. The silane hydrolysate utilizes a two-component silane material to improve the corrosion resistance of the coating. Detailed Implementation

[0015] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0016] In the experiment, the specific chemical composition of the austenitic stainless steel wire rod, by mass percentage, included 17.05% Ni, 14.67% Cr, 5.88% Si, 1.03% Mo, 1.28% Mn, 0.018% C, 0.020% P, 0.004% S, 0.03% Ce, and the balance being Fe; Pickling is performed using 15% hydrochloric acid for 60 seconds; the phosphating solution is made up of 25% phosphoric acid, 5% zinc oxide, 24% zinc nitrate, 3% calcium nitrate, 3% sodium nitrite, and deionized water to a final volume of 100%, and is treated for 60 seconds. The sealing coating was purchased from Nanjing Kerun Industrial Co., Ltd., model KR-SS910. Use Meten WRG3600 lubricating grease; The preparation steps for chromium-free zinc-aluminum coating solution are as follows: Step s1: Dissolve zirconium nitrate in deionized water by stirring. Add ethanol and silane coupling agent sequentially, adjust the pH to 4, stir at 35°C for 1 hour, and let stand for hydrolysis overnight to obtain silane hydrolysate. The volume ratio of silane coupling agent, ethanol, and deionized water is 1:1:8. Zirconium nitrate accounts for 0.5% of the silane hydrolysate. The silane coupling agent is a combination of silane coupling agent Si-69 and octadecyltrimethoxysilane in a volume ratio of 2:1. Step s2: Mix the modified sheet zinc-aluminum alloy powder and ethylene glycol, add deionized water and Tween-20 in sequence and stir evenly, then add modified graphene, hydroxyethyl cellulose, corrosion inhibitor and binder, and continue stirring at 150 r / min for 30 min to obtain metal slurry; wherein the corrosion inhibitor is sodium molybdate and the binder is acrylic resin. Step s3: Mix the silane hydrolysate obtained in steps s1 and s2 with the metal slurry, stir at 1500 r / min for 2 h, add defoamer, and continue stirring at 150 r / min for 30 min until no bubbles are present, to obtain chromium-free zinc-aluminum coating liquid; wherein the defoamer is sodium chloride.

[0017] The preparation steps of the modified flake zinc-aluminum alloy powder are as follows: The flake zinc-aluminum alloy powder was pretreated by placing it in anhydrous ethanol and ultrasonically cleaning it for 10 min, then rinsing and drying it. 6 g of silane coupling agent KH570, 80 mL of anhydrous ethanol, and 20 mL of deionized water were mixed and stirred to adjust the pH to 4. The mixture was stirred at 35°C for 1 h and allowed to stand for hydrolysis overnight to obtain a KH570 hydrolysate. 5 g of the pretreated flake zinc-aluminum alloy powder was mixed with the above KH570 hydrolysate and stirred at 40°C for 3 h. Then, 1.5 g of acrylic acid and 0.05 g of azobisisobutyronitrile diluted in 10 mL of anhydrous ethanol were added. The mixture was heated to 70°C and stirred for another 6 h. After filtration and washing, the modified flake zinc-aluminum alloy powder was obtained.

[0018] The flake-shaped zinc-aluminum alloy powder ZnAl2O used above was purchased from Hunan Sanliujiu Metallurgy, with a flake diameter of 15-20μm; The preparation steps of modified graphene are as follows: 0.6g of nickel nitrate hexahydrate and 0.5g of rare earth nitrate are added to 100mL of deionized water and sonicated for 20min. 0.5g of graphene oxide is placed in 20mL of deionized water, sonicated and dispersed, then 0.16g of sodium citrate is added and stirred for 10min. The mixture is then placed in the above nitrate solution and sonicated for 20min. The mixture is then transferred to a reaction vessel and reacted at 180℃ for 12h. After cooling to room temperature, the mixture is washed and freeze-dried to obtain the modified graphene. The rare earth nitrate is lanthanum nitrate, and the graphene oxide particle size is 2-3nm.

[0019] Example 1: This example provides a method for preparing a long-life stainless steel wire rope resistant to seawater corrosion. The specific steps are as follows: Step 1: Select austenitic stainless steel wire rod and place it in a high-temperature furnace for heat treatment. The temperature is increased to 1200℃ at a rate of 10℃ / s, held for 8 hours, and then cooled to room temperature with water. Pickling and phosphating are carried out in sequence, and then the wire is drawn in 7 consecutive passes to obtain a pre-drawn stainless steel wire with a specification of 10mm. Step 2: After degreasing and washing the pre-stretched stainless steel wire obtained in Step 1, hot-dip galvanize it to obtain a zinc coating with a mass of 225g / m. 2 After wiping and cooling, the wire is annealed for 3 hours at a temperature of 1000℃. After annealing, it is continuously drawn 10 times to obtain a finished stainless steel wire with a specification of 2.25mm. Step 3: After degreasing and washing the finished stainless steel wire obtained in Step 2, dip it into a chromium-free zinc-aluminum coating solution, spin dry, bake and cure to obtain a coating thickness of 30μm. After cooling, dip it into a sealing coating and dry to obtain a sealing coating thickness of 20μm. Then, apply lubricating grease at a rate of 100mL / m. 2 Parallel twisting is used to obtain stainless steel wire rope with an 8×61 structure.

[0020] The chromium-free zinc-aluminum coating liquid comprises the following raw materials by weight percentage: 20% modified flake zinc-aluminum alloy powder, 0.3% modified graphene, 8% ethylene glycol, 6% Tween-20, 2% hydroxyethyl cellulose, 2.0% sodium molybdate, 12% acrylic resin, 2% sodium chloride, 40% silane hydrolysate, and deionized water to bring the total to 100%. The baking and curing process includes pre-baking at 80°C for 10 minutes, followed by baking at 300°C for 12 minutes for curing.

[0021] Example 2: This example provides a method for preparing a long-life stainless steel wire rope resistant to seawater corrosion. The specific steps are as follows: Step 1: Select austenitic stainless steel wire rod and place it in a high-temperature furnace for heat treatment. The temperature is increased to 1200℃ at a rate of 10℃ / s, held for 8 hours, and then cooled to room temperature with water. Pickling and phosphating are carried out in sequence, and then the wire is drawn in 7 consecutive passes to obtain a pre-drawn stainless steel wire with a specification of 10mm. Step 2: After degreasing and washing the pre-stretched stainless steel wire obtained in Step 1, hot-dip galvanize it to obtain a zinc coating with a mass of 225g / m. 2 After wiping and cooling, the wire is annealed for 3 hours at a temperature of 1000℃. After annealing, it is continuously drawn 10 times to obtain a finished stainless steel wire with a specification of 2.25mm. Step 3: After degreasing and washing the finished stainless steel wire obtained in Step 2, dip it into a chromium-free zinc-aluminum coating solution, spin dry, bake and cure to obtain a coating thickness of 30μm. After cooling, dip it into a sealing coating and dry to obtain a sealing coating thickness of 20μm. Then, apply lubricating grease at a rate of 100mL / m. 2 Parallel twisting is used to obtain stainless steel wire rope with an 8×61 structure.

[0022] The chromium-free zinc-aluminum coating liquid comprises the following raw materials by weight percentage: 15% modified flake zinc-aluminum alloy powder, 0.1% modified graphene, 8% ethylene glycol, 6% Tween-20, 2% hydroxyethyl cellulose, 2.0% sodium molybdate, 12% acrylic resin, 2% sodium chloride, 35% silane hydrolysate, and deionized water to bring the total to 100%. The baking and curing process includes pre-baking at 80°C for 10 minutes, followed by baking at 270°C for 15 minutes for curing.

[0023] Example 3: This example provides a method for preparing a long-life stainless steel wire rope resistant to seawater corrosion. The specific steps are as follows: Step 1: Select austenitic stainless steel wire rod and place it in a high-temperature furnace for heat treatment. The temperature is increased to 1200℃ at a rate of 10℃ / s, held for 8 hours, and then cooled to room temperature with water. Pickling and phosphating are carried out in sequence, and then the wire is drawn in 7 consecutive passes to obtain a pre-drawn stainless steel wire with a specification of 10mm. Step 2: After degreasing and washing the pre-stretched stainless steel wire obtained in Step 1, hot-dip galvanize it to obtain a zinc coating with a mass of 225g / m. 2 After wiping and cooling, the wire is annealed for 3 hours at a temperature of 1000℃. After annealing, it is continuously drawn 10 times to obtain a finished stainless steel wire with a specification of 2.25mm. Step 3: After degreasing and washing the finished stainless steel wire obtained in Step 2, dip it into a chromium-free zinc-aluminum coating solution, spin dry, bake and cure to obtain a coating thickness of 30μm. After cooling, dip it into a sealing coating and dry to obtain a sealing coating thickness of 20μm. Then, apply lubricating grease at a rate of 100mL / m. 2 Parallel twisting is used to obtain stainless steel wire rope with an 8×61 structure.

[0024] The chromium-free zinc-aluminum coating liquid comprises the following raw materials by weight percentage: 20% modified flake zinc-aluminum alloy powder, 0.2% modified graphene, 8% ethylene glycol, 6% Tween-20, 2% hydroxyethyl cellulose, 2.0% sodium molybdate, 12% acrylic resin, 2% sodium chloride, 35% silane hydrolysate, and deionized water to bring the total to 100%. The baking and curing process includes pre-baking at 80°C for 10 minutes, followed by baking at 300°C for 12 minutes for curing.

[0025] Example 4: This example provides a method for preparing a long-life stainless steel wire rope resistant to seawater corrosion. The specific steps are as follows: Step 1: Select austenitic stainless steel wire rod and place it in a high-temperature furnace for heat treatment. The temperature is increased to 1200℃ at a rate of 10℃ / s, held for 8 hours, and then cooled to room temperature with water. Pickling and phosphating are carried out in sequence, and then the wire is drawn in 7 consecutive passes to obtain a pre-drawn stainless steel wire with a specification of 10mm. Step 2: After degreasing and washing the pre-stretched stainless steel wire obtained in Step 1, hot-dip galvanize it to obtain a zinc coating with a mass of 225g / m. 2 After wiping and cooling, the wire is annealed for 3 hours at a temperature of 1000℃. After annealing, it is continuously drawn 10 times to obtain a finished stainless steel wire with a specification of 2.25mm. Step 3: After degreasing and washing the finished stainless steel wire obtained in Step 2, dip it into a chromium-free zinc-aluminum coating solution, spin dry, bake and cure to obtain a coating thickness of 30μm. After cooling, dip it into a sealing coating and dry to obtain a sealing coating thickness of 20μm. Then, apply lubricating grease at a rate of 100mL / m. 2 Parallel twisting is used to obtain stainless steel wire rope with an 8×61 structure.

[0026] The chromium-free zinc-aluminum coating solution comprises the following raw materials by weight percentage: 20% modified flake zinc-aluminum alloy powder, 0.3% modified graphene, 8% ethylene glycol, 6% Tween-20, 2% hydroxyethyl cellulose, 2.0% sodium molybdate, 12% acrylic resin, 2% sodium chloride, 40% silane hydrolysate, and deionized water to bring the total to 100%. The baking and curing process includes pre-baking at 80°C for 10 minutes, followed by baking at 320°C for 15 minutes for curing.

[0027] Comparative Example 1: A control experiment of Example 1, in which the flake zinc-aluminum alloy powder was not modified. The specific steps are as follows: Step 1: Select austenitic stainless steel wire rod and place it in a high-temperature furnace for heat treatment. The temperature is increased to 1200℃ at a rate of 10℃ / s, held for 8 hours, and then cooled to room temperature with water. Pickling and phosphating are carried out in sequence, and then the wire is drawn in 7 consecutive passes to obtain a pre-drawn stainless steel wire with a specification of 10mm. Step 2: After degreasing and washing the pre-stretched stainless steel wire obtained in Step 1, hot-dip galvanize it to obtain a zinc coating with a mass of 225g / m. 2 After wiping and cooling, the wire is annealed for 3 hours at a temperature of 1000℃. After annealing, it is continuously drawn 10 times to obtain a finished stainless steel wire with a specification of 2.25mm. Step 3: After degreasing and washing the finished stainless steel wire obtained in Step 2, dip it into a chromium-free zinc-aluminum coating solution, spin dry, bake and cure to obtain a coating thickness of 30μm. After cooling, dip it into a sealing coating and dry to obtain a sealing coating thickness of 20μm. Then, apply lubricating grease at a rate of 100mL / m. 2 Parallel twisting is used to obtain stainless steel wire rope with an 8×61 structure.

[0028] The chromium-free zinc-aluminum coating solution comprises the following raw materials by weight percentage: 20% flake zinc-aluminum alloy powder, 0.3% modified graphene, 8% ethylene glycol, 6% Tween-20, 2% hydroxyethyl cellulose, 2.0% sodium molybdate, 12% acrylic resin, 2% sodium chloride, 40% silane hydrolysate, and deionized water to bring the total to 100%. The baking and curing process includes pre-baking at 80°C for 10 minutes, followed by baking at 300°C for 12 minutes for curing.

[0029] Comparative Example 2: A control experiment of Example 1, without the addition of modified graphene. The specific steps are as follows: Step 1: Select austenitic stainless steel wire rod and place it in a high-temperature furnace for heat treatment. The temperature is increased to 1200℃ at a rate of 10℃ / s, held for 8 hours, and then cooled to room temperature with water. Pickling and phosphating are carried out in sequence, and then the wire is drawn in 7 consecutive passes to obtain a pre-drawn stainless steel wire with a specification of 10mm. Step 2: After degreasing and washing the pre-stretched stainless steel wire obtained in Step 1, hot-dip galvanize it to obtain a zinc coating with a mass of 225g / m. 2 After wiping and cooling, the wire is annealed for 3 hours at a temperature of 1000℃. After annealing, it is continuously drawn 10 times to obtain a finished stainless steel wire with a specification of 2.25mm. Step 3: After degreasing and washing the finished stainless steel wire obtained in Step 2, dip it into a chromium-free zinc-aluminum coating solution, spin dry, bake and cure to obtain a coating thickness of 30μm. After cooling, dip it into a sealing coating and dry to obtain a sealing coating thickness of 20μm. Then, apply lubricating grease at a rate of 100mL / m. 2 Parallel twisting is used to obtain stainless steel wire rope with an 8×61 structure.

[0030] The chromium-free zinc-aluminum coating solution comprises the following raw materials by weight percentage: 20% modified flake zinc-aluminum alloy powder, 8% ethylene glycol, 6% Tween-20, 2% hydroxyethyl cellulose, 2.0% sodium molybdate, 12% acrylic resin, 2% sodium chloride, 40% silane hydrolysate, and deionized water to bring the total to 100%. The baking and curing process includes pre-baking at 80°C for 10 minutes, followed by baking at 300°C for 12 minutes for curing.

[0031] Testing and Experiment 1. Corrosion Resistance Test: Prepare an artificial seawater solution with the following concentrations: NaCl 24.53 g / L, Na2SO4 4.09 g / L, NaHCO3 0.201 g / L, KCl 0.695 g / L, MgCl2·6H2O 11.1 g / L, CaCl2 1.16 g / L, KBr 0.101 g / L, and 1 L H2O. Adjust the pH of the solution to 8.2 by adding NaOH. Immerse 1 m of the samples prepared in Examples 1-4 and Comparative Examples 1-2 in the above-mentioned artificial seawater solution at 25°C. Replace the solution every 3 hours until pitting corrosion appears on the test surface, and record the time. 2. Breaking tensile strength test: According to GB / T 38814, take the steel wire ropes made in Examples 1-4 and Comparative Examples 1-2, cut 3m as the most effective test section length, clamp the specimen, and test it on a static fatigue machine. Apply a load of 200N and set the fatigue cycle to 5000. After 5000 cycles, apply tensile force to the specimen until it breaks. The data is recorded in the table below.

[0032]

[0033] In summary, the experimental data above show that the coating formulation used in Example 1 achieved better experimental results than the other examples, exhibiting excellent seawater corrosion resistance and a service life of up to 58 days. Comparative Example 1 served as a control experiment for Example 1, without applying any coating modification treatment to the zinc-aluminum alloy powder, resulting in a significant decrease in corrosion resistance, similar to the results of Comparative Example 2 without the addition of modified graphene. However, the decrease in breaking tensile strength was not significant because the peeling of the coating resulted in the subsequent test results of the wire rope being reflected in the main material of the wire rope, thus the decrease was not obvious. In conclusion, the stainless steel wire rope produced by this invention possesses excellent seawater corrosion resistance and fatigue resistance.

[0034] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

Claims

1. A method for preparing a long-life stainless steel wire rope resistant to seawater corrosion, characterized in that, Specifically, the following steps are included: Step 1: Select austenitic stainless steel wire rod, and perform heat treatment, pickling, and phosphating in sequence, and then draw it through 7 consecutive draws to obtain pre-drawn stainless steel wire with a specification of 8-10mm. Step 2: After degreasing and washing the pre-drawn stainless steel wire obtained in Step 1, hot-dip galvanize it, wipe it to cool it, and then anneal it. After annealing, it is drawn again for 8-10 consecutive times to obtain finished stainless steel wire with a specification of 1-3mm. Step 3: After degreasing and washing the stainless steel wire obtained in Step 2, dip it in a chromium-free zinc-aluminum coating solution, spin dry, bake and cure to obtain a coating thickness of 30μm. After cooling, dip it in a sealing coating, dry it and then coat it with lubricating grease. Then, use parallel twisting to obtain a stainless steel wire rope. The specific chemical composition of the austenitic stainless steel wire rod in step 1, by mass percentage, includes 16-18% Ni, 14.5-14.7% Cr, 5.5-6.0% Si, 1.02-1.05% Mo, 1.08-1.30% Mn, C≤0.020%, P≤0.020%, S≤0.004%, 0.01-0.05% Ce, and the balance being Fe; The chromium-free zinc-aluminum coating solution in step 3 comprises the following raw materials by mass percentage: 15-20% modified flake zinc-aluminum alloy powder, 0.1-0.3% modified graphene, 8-10% ethylene glycol, 6-8% Tween-20, 1-2% hydroxyethyl cellulose, 1.5-2.0% corrosion inhibitor, 10-15% binder, 1-2% defoamer, 30-40% silane hydrolysate, and deionized water to bring the total to 100%. The preparation steps of the modified flake zinc-aluminum alloy powder are as follows: The flake zinc-aluminum alloy powder is pretreated by placing it in anhydrous ethanol, ultrasonically cleaning it for 10 min, rinsing and drying it; silane coupling agent KH570, anhydrous ethanol and deionized water are mixed and stirred, the pH is adjusted to 4, and the mixture is stirred at 35°C for 1 h, and allowed to stand for hydrolysis overnight to obtain KH570 hydrolysate; the pretreated flake zinc-aluminum alloy powder is mixed with the above KH570 hydrolysate, stirred at 40°C for 3 h, an acrylic acid solution diluted with anhydrous ethanol and azobisisobutyronitrile are added, the temperature is raised to 70°C, and stirring is continued for 6 h; the mixture is filtered and washed to obtain the modified flake zinc-aluminum alloy powder. The preparation steps of the modified graphene are as follows: nickel nitrate hexahydrate and rare earth nitrate are added to deionized water and ultrasonicated for 20 min for later use; graphene oxide is placed in deionized water, ultrasonically dispersed, sodium citrate is added and stirred for 10 min, placed in the above nitrate solution and ultrasonicated for 20 min, then transferred to a reaction vessel and reacted at 160-180℃ for 12 h, cooled to room temperature, washed and freeze-dried to obtain the modified graphene; wherein the rare earth nitrate is any one of cerium nitrate, lanthanum nitrate and yttrium nitrate.

2. The method for preparing a long-life, seawater-resistant stainless steel wire rope according to claim 1, characterized in that, In step 1, the heat treatment involves heating to 1150-1200℃ at a rate of 10℃ / s, holding at that temperature for 8-12 hours, and then water-cooling to room temperature. In step 2, the zinc layer obtained by hot-dip galvanizing has a zinc surface mass of 200-240g / m². 2 The annealing temperature is 1000-1100℃ and the annealing time is 2-3 hours.

3. The method for preparing a long-life, seawater-resistant stainless steel wire rope according to claim 1, characterized in that, The baking and curing process includes pre-baking at 80-100℃ for 8-10 minutes, followed by baking at 270-320℃ for 12-15 minutes for curing.

4. The method for preparing a long-life, seawater-resistant stainless steel wire rope according to claim 1, characterized in that, The preparation steps of the chromium-free zinc-aluminum coating solution are as follows: Step s1: Place zirconium nitrate in deionized water, stir to dissolve, add ethanol and silane coupling agent in sequence, adjust pH to 4-5, stir at 35℃ for 1 hour, let stand for hydrolysis overnight to obtain silane hydrolysate; Step s2: Mix the modified sheet zinc-aluminum alloy powder and ethylene glycol, add deionized water and Tween-20 in sequence and stir evenly, then add modified graphene, hydroxyethyl cellulose, corrosion inhibitor and binder, and continue stirring at 150 r / min for 30 min to obtain metal slurry; Step s3: Mix the silane hydrolysate obtained in steps s1 and s2 with the metal slurry, stir at 1500 r / min for 2-3 h, add the defoamer, and continue stirring at 150 r / min for 20-30 min to obtain the chromium-free zinc-aluminum coating solution.

5. The method for preparing a long-life, seawater-resistant stainless steel wire rope according to claim 4, characterized in that, In step s1, the silane coupling agent is one or a combination of two of the following: bis-[γ-(triethoxysilane)propyl]-tetrasulfide silane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane, and octadecyltrimethoxysilane.

6. The stainless steel wire rope prepared by the method according to any one of claims 1-5, characterized in that, The stainless steel wire rope has an 8×61 structure and a nominal diameter of 96mm, including a core and outer strands; the outer strands adopt a 61FWS structure; the core consists of an outer core strand and a core center strand, both of which adopt a 36WS structure.

Citation Information

Patent Citations

  • High-strength austenitic stainless steel for automobile frames and manufacturing method thereof

    CN104120368A

  • Method for manufacturing highly corrosion-resistant steel wire rope for fishery

    CN104928956A

  • Preparation method of high-safety multi-strand stainless steel wire rope

    CN117758529A

  • Low-temperature-resistant alloy steel end socket and preparation process thereof

    CN118027765A